Residual SARS-CoV-2 RNA in nasal swabs of convalescent COVID-19 patients: Is prolonged quarantine always justified?. (January 2021) - Piralla, Antonio; Ricchi, Matteo; Cusi, Maria Grazia; Prati, Paola; Vicari, Nadia; Scarsi, Giada; Gandolfo, Claudia; Anichini, Gabriele; Terrosi, Chiara; Percivalle, Elena; Vecchio Nepita, Edoardo; Bergami, Federica; et al.
Highlights: Persistent SARS-CoV-2 RNA detection resulted in prolonged quarantine. In less than 3% of clinical samples with a high quantification cycle value (>30), cultivable virus was detected. NGS analysis showed a fragmented genome, indicating no functional residual RNA. Abstract: Real-time reverse transcription PCR is currently the most sensitive method to detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Defining whether a patient could be contagious or not contagious in the presence of residual SARS-CoV-2 RNA is of extreme importance in the context of public health. In this prospective multicenter study, virus isolation was prospectively attempted in 387 nasal swabs from clinically recovered patients showing low viral load (quantification cycle, Cq, value greater than 30). The median Cq value was 36.8 (range 30.0–39.4). Overall, a cytopathic effect was detected in nine samples, corresponding to a culture positivity rate of 2.3% (9/387). The results of this study help to dissect true virus replication and residual viral RNA detection in recovered patients.